(untitled) (Journal Of Educational and Psychological Researches, 2022)
The current research aims to identify the occupational stresses of doctors who are working in governmental hospitals according to the variables of gender and career ranking. The researcher adopted a scale to measure the occupational stress of (1088) doctors (561 males and 527 females) working in governmental hospitals. The results have shown that doctors have a high level of professional stress, but there is no significant difference between doctors in terms of gender. However, there were significant differences in favor of novice residents.